Improvement of Wash Performance and Energy Efficiency in Top Load Washers - Shukla, Girish Kumar (My University, 2022)
Washing performance and energy consumption of a washer has been considered as the center of concern for the industry of household washers. This work comprises the detailed evaluation of the factors and parameters involved in the result of the wash quality and the energy consumption, algorithm study and modification and the proposal of the effective design changes in the dynamic parts of the top loader back panel washing machine. For the comparison study, reference machine called WascatorFOM71CLS is used for 8kg top load washer. Test runs have been conducted after considering the treatments finalized through Design of Experiment (DOE). Results are obtained by conducting the performance test as per IEC 60456:2010 and Schedule 12 of Bureau of Energy Efficiency for wash quality and energy results. Optimization involved three factors i.e. wash time, motor on-time and water quantity. All the inputs are as per the IEC standard starting from the load conditioning to the result calculation. Running high wash time, high On-time and high water quantity contributed most optimized results considering both the fore mentioned objectives. Taking these results forward new stain removal dedicated program developed named Stain Master+ and tested accordingly in the laboratory. Also for the objective of the improved wash performance and optimized energy consumption, design changes in the most dynamic part of the washer called Pulsator. Algorithm of the new stain master+ program has been modified from the existing Strong Wash Program. Structural and CFD analysis is done for the comparison of the existing and new pulsator design with turbulent intensity
Keywords: Design of Experiment; Top loader; IEC; BEE; Wascator; Algorithm; Pulsator; Turbulent intensity